Sequential capillarity-assisted particle assembly in a microfluidic channel. Issue 5 (11th January 2021) - Pioli, Roberto; Fernandez-Rodriguez, Miguel Angel; Grillo, Fabio; Alvarez, Laura; Stocker, Roman; Isa, Lucio; Secchi, Eleonora
Abstract : Exploiting capillarity, a new microfluidic platform enables the placement of multiple colloidal particles into complex patterns within a microchannel, as required in a variety of applications, including electronics, sensing, and plasmonics. Abstract : Colloidal patterning enables the placement of a wide range of materials into prescribed spatial arrangements, as required in a variety of applications, including micro- and nano-electronics, sensing, and plasmonics. Directed colloidal assembly methods, which exploit external forces to place particles with high yield and great accuracy, are particularly powerful. However, currently available techniques require specialized equipment, which limits their applicability. Here, we present a microfluidic platform to produce versatile colloidal patterns within a microchannel, based on sequential capillarity-assisted particle assembly (sCAPA). This new microfluidic technology exploits the capillary forces resulting from the controlled motion of an evaporating droplet inside a microfluidic channel to deposit individual particles in an array of traps microfabricated onto a substrate. Sequential depositions allow the generation of a desired spatial layout of colloidal particles of single or multiple types, dictated solely by the geometry of the traps and the filling sequence. We show that the platform can be used to create a variety of patterns and that the microfluidic channel easily allows surface functionalization of trapped particles. By enabling colloidal patterning to be carried out in a controlled environment, exploiting equipment routinely used in microfluidics, we demonstrate an easy-to-build platform that can be implemented in microfluidics labs.